Effect of Promoting Self Care Ability Program on Knowledge and Self-Care Behavior of Chronic Obstructive Pulmonary Disease Patients With Recurrent Acute Exacerbation - Worawichianwong, Sirirat; Siripitayakunkit, Apinya; Kanogsunthornrat, Nirobol (Journal of The Royal Thai Army Nurses, 2021)
This study is one-group quasi-experimental research (pretest-posttest design). The purpose of this study was to examine the effects of promoting self-care ability program on knowledge and self-care behavior of chronic obstructive pulmonary disease (COPD) patients with recurrent acute exacerbation. Orem’s Self-Care Theory was used as the theoretical framework, and Motivational Interviewing were applied to guide the study. Purposive sampling was used to recruit 30 research participants. The data were analyzed using descriptive statistics and non-parametric Wilcoxon-rank test. The results revealed after receiving the program, the mean of participants’ COPD knowledge scores significantly increased from 9.03 to 13.87% (p < .05 and their self-care behavior scores significantly improved from 61.70 to 94.60 (p < .05). Regarding inhaler using techniques, the participants demonstrated correct using techniques for Handihaler, Accuhaler, and Turbuhaler in every step and showed improvement in the use of Metered Dose Inhaler (MDI). Nurses play a vital role in promoting the patients to perform appropriate self-care behaviors continuously and sustainably.